Design and Simulation of Photovoltaic Array - Antani, Tithi Anish; Kumar, Ujjwal; Bhat, Sindhu K.; Mishra, Soumya (Asian Journal of Electrical Sciences, 2019)
This paper illustrates a simple yet accurate method of modelling photovoltaic array. By adjusting the curve at three points: open circuit, maximum power, and short circuit, the parameter of the nonlinear equation can be determined. The information about these three major points is provided by all commercial array datasheets, using this data we can easily find the best I-V equation for the single-diode photovoltaic (PV) model. Adjusting the parameters of I–V equation, one can build a PV circuit model with any circuit simulator by using basic math blocks. The proposed circuit model and modeling method and are useful for power electronics designers who need a simple, fast, accurate, and easy-to-use modeling method for using in simulations of PV systems.